PMO-211 Propofol sedation for colonoscopy: a single centre's experience. (28th May 2012) - Rogers, D; Robinson, R; Shah, S
Abstract : Introduction: GI endoscopy has been widely practiced for nearly 40 years. Techniques and sedation regimes have advanced together with an ever increasing complexity of therapeutic possibilities. Despite improved colonoscopic technique there remain a small number of patients who cannot tolerate colonoscopy. We introduced propofol endoscopy lists for difficult patients and complex therapeutic work. The lists are run by an anaesthetist and aim to ensure that the most technically challenging patients are comfortable, relaxed and compliant during the procedure. We review the success and complications of colonoscopy under propofol in our centre. Methods: Review of the last 100 consecutive colonoscopies performed under propofol at Leicester General Hospital. Data were analysed for demographics, indications, diagnoses, propofol dose, reason for the use of propofol and complications. Polyp detection figures were compared to JAG standards and we assessed completion rates in those who had had a failed procedure under conscious sedation previously. Results: 100 procedures were analysed and the patients' age ranged from 20 to 84 years with 70% female and 30% male. Mean propofol dose was 328 mg. 66 patients had had a previous colonoscopy of which 50% had been failed. In the other 50% a variety of reasons were given for propofol use. Of the 34 patients who had not undergone previous colonoscopy the reason for using propofol was only clear in 9. Polyps were detected in 29% of procedures and 89% were completed successfully. 85% of procedures in those patients who had previously failed colonoscopy under sedation were successful. Poor bowel prep prevented completion in three cases, and therefore if these are excluded 93% of colonoscopies previously failed under conscious sedation were successful with propofol. One procedure that had been successful, but difficult, using conscious sedation was unsuccessful using propofol. This may relate to difficulties turning anaesthetised patients. One patient died within 30 day of their procedure. They had extensive ischaemic colitis and significant cardiac comorbidities. Conclusion: There has been a sustained demand for propofol sedation within UHL, and it appears to be well-tolerated and safe in appropriately selected patients. High risk patients should be identified and directed to more appropriate diagnostic modalities. It is important to remember that propofol is not a panacea, and we describe a procedure that had been "tricky" using conscious sedation becoming impossible when performed under propofol. Propofol has a role to play in complex therapeutic work and in those who cannot otherwise tolerate the procedure due to pain. Propofol lists are popular with patients, and as complex therapeutic endoscopy expands it is likely that all hospitals will need a similar service, but an appropriately negotiated tariff is necessary to take account of increased costs. Competing interests: None declared.